(3YbhO GdCTZGd GdYGeI habB dfXGe JSdje GdeaJGM (B: s (3OQGSI ebGQfI (B/ s - (3jMji eMeO YjO eQSi GdfeQs; (3LGHQ LGO fUGQs; (3eMeO MSfjf YHOGdYGds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3ai YbhO GdCTZGd GdYGeI HfXGe JSdje GdeaJGM jJe GdGJaGb ai ZGdHjI Jdc GdYbhO Ydi GdJMcje chSjdI daV GdefGRYGJ GdJi JKhQ HSHH Jdc GdYbhO HYOeG HOC jJbdU OhQ GdbVGA GdEOGQi ai GdaUd ai efGRYGJ GdYbhO GdEOGQjI aZGdHB eGJchf YbhO GdCTZGd GdYGeI HfXGe JSdje GdeaJGM ef GdYbhO GdOhdjI MjK jchf GdebGhd YHGQI TQcI ebGhdGJ CLfHjI Ch JLeY EJaGbi Hjf CcKQ ef TQcI ebGhdGJ (B: (3hYbhO GdCTZGd GdYGeI HGdeaghe GdJbdjOi hcPdc ai GdCWQ GdMOjKI JJejR HCfgG ef YbhO GdeOI aJSJZQb hbJB WhjdB dJfajPgG bO jeJO Edi YOI SfhGJs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2010s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B519-552s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdJMcje ai GdYbhO GdEOGQjIs; (3YbhO GdCTZGd GdYGeIs; (3YbhO JSdje GdeaJGMs; (3YbhO GdajOjcs; (3GgdjI GdTNU GdWHjYjs; (3GTNGU GdJYGbOs; (3GgejI GdeaGhVGJs; (3GdJRGeGJ GdeJYGbOjf s; (3GdGdJRGe HGdJSdjes; (3GdGdJRGe HGdVeGfs; (3GdXQha GdWGQFIs; (3fXQjg Yed GdGejQs; (3hSGFd JShjI GdefGRYGJs; (3OYhI HWdGf GdYbOs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes